The Expressive Speech Act on Ridwan Kamil’s Comments in Instagram Posting about First COVID-19 Case in Indonesia - Yulia Anggraeni; Lia Maulia Indrayani; Ypsi Soeria Soemantri (Universitas Bengkulu, 2020)
In the early time of the president’s announcement about the first patient infected the Coronavirus in Indonesia, a governor of West Java, Ridwan Kamil, uploaded the information of the president’s announcement in his Instagram account @ridwankamil. The Instagram post received many comments as responses from his followers. Regarding the issue, this study aims at seeing the netizens' responses to the news about the first patient who infected the Coronavirus in Indonesia, Ridwan Kamil posted on Instagram through the theory of expressive speech act. In this research, the researchers used qualitative descriptive research. The instruments of this research are observation and document. Random sampling is used as a Data collection technique. The researchers organizes the data by choosing the comments on Ridwan Kamil’s Instagram posting randomly, then the researchers tried to find out, selected, and classified the expressive speech acts used by netizens. The last, researchers explained the result of the analysis. As a result, the researchers found that the responses given by netizens on Instagram contained an expression of wishing, expression of complaining, and expression of protest. Through the comments written by netizens, they tries to give the aspiration to the government to solve the problems that citizens complained or protested about the COVID-19.